GALICS III: Predicted properties for Lyman Break Galaxies at redshift 3 - Blaizot, J; Guiderdoni, B; Devriendt, J; Bouchet, F; Hatton, S; Stoehr, F (2003)
This paper illustrates how mock observational samples of high-redshift galaxies with sophisticated selection criteria can be extracted from the predictions of GALICS, a hybrid model of hierarchical galaxy formation that couples the outputs of large cosmological simulations and semi-analytic recipes to describe dark matter collapse and the physics of baryons respectively. As an example of this method, we focus on the properties of Lyman Break Galaxies at redshift 3. With the MOMAF software package described in a companion paper, we generate a mock observational sample with selection criteria as similar as possible to those implied in the actual observations of z = 3 LBGs by Steidel et al.(1995). Our model predictions are in good agreement with the observed number density and 2D correlation function. We investigate the optical/IR luminosity budget as well as several other physical properties of LBGs and find them to be in general agreement with observed values. Looking into the future of these LBGs we predict that 75% of them end up as massive ellipticals today, even though only 35% of all our local ellipticals are predicted to have a LBG progenitor. In spite of some shortcomings, this new 'mock observation' method clearly represents a necessary first step toward a more accurate comparison between hierarchical models of galaxy formation and real observational surveys.